Prevalence and Serotypes diversity of Salmonella Species in the Nile Perch (Lates niloticus) of the Lake Victoria, Tanzania - Ally, Mohamed Hamed Sango (Journal of Biology and Life Science, 2022)
A cross-sectional study was conducted to estimate the prevalence, serotypes, antimicrobial resistance and plasmids profiles of Salmonella spp. in Nile perch of Lake Victoria, Tanzania. Salmonella spp. and Escherichia coli in water and fish samples were investigated by the bacteriological methods. Antimicrobial resistance profiles of Salmonella spp. were determined using the minimum inhibitory concentration (MIC) method. A total of 324 samples were analysed including Nile perch, water and swabs from surfaces of facilities used for fish transport. The finding showed the prevalence of Salmonella spp. in fish at fishing ground were 16/60 (26.7%), landing sites and markets were 9/60 (15%) and 18/60 (30%) respectively. A significant difference (p<0.05) was observed between the prevalence of Salmonella spp. in fish from fishing ground and those at landing sites, but not with those from markets (p>0.05). The main serotypes recovered were Salmonella ser. Waycross (41: z4z23 :-) and Salmonella enterica ssp. salamae (42: r :-). Most Salmonella serotypes showed the low resistance profiles against most of antimicrobials, but few isolates were resistant to Nalidixic acid 3/64 (4.7%), ampicillin 5/64 (7.8%), azithromycin 14/64 (21.9%) and sulfamethoxazole 22/64 (34.4%). Plasmids were detected in few Salmonella ser. Waycross compared to none of Salmonella ssp. salamae. Escherichia coli count ranged 0.77 to 2.44 log10 cfu/g in fish and 0.44 to 1.71 log10 cfu/ml in water. Contaminated fish with different Salmonella serovars imply pollution of the lake attributable to waste from point and nonpoint sources that may contain antibiotic residues accounting for resistant bacteria in aquatic environment. Un-hygienic fish handling and poor conditions of markets account for the high prevalence of Salmonella spp. in Nile perch at markets.